2009
DOI: 10.1002/anie.200901249
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stereoselective One‐Pot Synthesis of Bicyclic Isoxazolidines with Five Stereogenic Centers by an Organocatalytic Process

Abstract: Dedicated to Professor Pierre Vogel on the occasion of his 65th birthday Intramolecular nitrone/alkene cycloadditions have received a great deal of attention as a useful methodology for the formation of the intriguing frameworks found in natural products and biologically interesting compounds.[1] The key feature of this approach is the suitable elaboration of the primary cycloadducts, which has proven to be a practical strategy for making different heterocyclic systems.[2] Owing to the labile nature of the NÀO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…[35,52,[54][55][56][57] One of the most widely used methods involves treatment of the isoxazolidine with Mo(CO) 6 and NaBH 4 . [29] Alternatively, Ji and Miller [58] and others [59][60][61][62] have previously shown that catalytic hydrogenation can be an effective route toward N-O reductive cleavage. Unfortunately for us, these methods led to intractable product mixtures or no observable reaction, respectively (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[35,52,[54][55][56][57] One of the most widely used methods involves treatment of the isoxazolidine with Mo(CO) 6 and NaBH 4 . [29] Alternatively, Ji and Miller [58] and others [59][60][61][62] have previously shown that catalytic hydrogenation can be an effective route toward N-O reductive cleavage. Unfortunately for us, these methods led to intractable product mixtures or no observable reaction, respectively (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…A one-pot synthesis of bicyclic isoxazolidines with five stereogenic centers by catalyst 12 was reported by Zhong and his co-workers, Scheme 3.85 [107]. This domino sequence involved Michael reaction of 7-oxohept-2-enoate 267 to nitroolefins 60 [108] and subsequent intramolecular nitrone [3 + 2] cycloaddition to give enantiopure bicyclic isoxazolidines 268.…”
Section: Multicomponent Reactions [102]mentioning
confidence: 98%
“…247 Reaction of 7-oxohept-2-enoate derivatives 395 with nitro-olens 15 were investigated by Zhong et al to give highly stereoselective bicyclic isoxazolidines 396 bearing ve stereogenic centers (Scheme 135). 248 The reaction proceeded via domino Michael addition/nitrone formation/intramolecular [3 + 2] nitrone-olen cycloaddition catalysed by 10 mol% of chiral a,adiphenyl prolinol trimethylsilyl ether Cat-8 and AcOH (20 mol%) as an additive. The products were obtained in good-toexcellent yields with excellent diastereo-and enantioselectivities of up to 94% de and >99% ee, respectively.…”
Section: And Benzene Ring In 127bmentioning
confidence: 99%